A Critique on Current Paradigms of Economic ‘Growth’ and ‘Development’ in the Context of Environment and Sustainability Issues - Roy, Sayan (Consilience, 2016)
This paper critically evaluates different models of economic progress and development using concepts based on the idea of the ‘political economy’. It explores the influence of globalization on these different models and explores the nexus between the International Financial Institutions, trade bodies, and agreements that continuously exert economic pressure on governments. This paper also attempts to understand the environment and society in the context of markets and valuation mechanisms, and questions the effectiveness of economic instruments used to tackle complex environmental issues such as climate change and deforestation. The rest of this paper focuses on the technology-market interface; technologically oriented economic solutions seem to have a limited understanding of the root causes of the issues they are created to remedy. They also fail to acknowledge the intricate relationship between humans and their environments. This paper expounds the perceived inability of conventional economic frameworks to capture the dynamism, complex interactions, and organic nature of life sustaining phenomena in the biosphere is emphasized.